RISK ANALISYS OF DEMERSAL FISHING USING FISH TRAP IN SERIBU ISLAND, JAKARTA - Vivi Septi Sari; Mustaruddin; Fis Purwangka (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2025)
Demersal fish capture activities using fish traps in the Seribu Islands have relatively high risks as they involve divers, the operation of simple compressors, and dynamic marine environmental conditions. This study aims to analyze the level of risk at each stage of trap fishing, including preparation, fishing operations, and post-fishing activities, as well as to formulate appropriate control measures. The methods applied was Formal Safety Assessment (FSA) to evaluate risks based on frequency and severity. The results showed that most activities were classified as high risk, with 16,7% in the preparation stage, 65,2% in the fishing operation stage, and 61,5% in the post-fishing operation stage, while the remaining activities were categorized as medium risk, and no activities were identified as low risk. Internal factors such as physical fatigue, lack of knowledge, and non-compliance with safety procedures, and external factors such as unfavorable weather and strong underwater currents, were identified as the dominant causes of high risk. Comprehensive risk control is therefore required through regular equipment maintenance, the implementation of safe work procedures, and the consistent use of personal protective equipment to enhance the safety of trap fishers in the Seribu Islands. Key words: fish trap, occupational safety, risk